2020
DOI: 10.3390/ma13051044
|View full text |Cite
|
Sign up to set email alerts
|

Biological Reactions to Metal Particles and Ions in the Synovial Layer of Mice

Abstract: Metal particles and ions released from implants not only have a fundamental effect on the longevity of total joint replacements, but can also be disseminated to remote organs. Periprosthetic tissues harvested during revision surgeries mainly reflect end-stage failure but may not adequately reveal initial biological reactions and systemic side effects. Therefore, primary reactions caused by metal particles and ions were investigated in an established murine model. Left knee joints in three groups, each consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Additionally, the aspect ratio (AR), equivalent circular diameter (ECD), and the roundness (R) of wear particles were determined utilizing scanning electron microscopy (SEM; Carl Zeiss, Oberkochen, Germany). According to our previous results, these generated particles have a mean size in the nanometer range (ECD: 61.25 ± 18.47 nm) with an aspect ratio of 1.69 ± 0.66 and a roundness of 0.64 ± 0.16 [34]. Additionally, the shape of metal particles was principally round and oval, accompanied by a small proportion of needle-shaped particles, similar to wear particles in retrieved tissues of revision surgeries [35,36].…”
Section: Co28cr6mo Particles/ions Generationmentioning
confidence: 52%
“…Additionally, the aspect ratio (AR), equivalent circular diameter (ECD), and the roundness (R) of wear particles were determined utilizing scanning electron microscopy (SEM; Carl Zeiss, Oberkochen, Germany). According to our previous results, these generated particles have a mean size in the nanometer range (ECD: 61.25 ± 18.47 nm) with an aspect ratio of 1.69 ± 0.66 and a roundness of 0.64 ± 0.16 [34]. Additionally, the shape of metal particles was principally round and oval, accompanied by a small proportion of needle-shaped particles, similar to wear particles in retrieved tissues of revision surgeries [35,36].…”
Section: Co28cr6mo Particles/ions Generationmentioning
confidence: 52%
“…However, in a study using a mouse model, the intraarticular injection of CoCrMo particles induced a significantly enhanced pro-inflammatory cytokine expression (TNF-α, IL-6, and IL-1β) when compared to the intraarticular injection of CoCrMo ions (Cheng et al, 2020). On the other hand, the expression of CD3-positive cells in the synovial membrane of mouse knee did not increase in any of the groups (Cheng et al, 2020). In the same line, data from an epidemiologic study showed that patients with MoM or MoP implants displayed a decrease in blood T lymphocytes despite an increase in the serum level of chromium and cobalt (Granchi et al, 2003).…”
Section: Metal Wear Debrismentioning
confidence: 95%
“…The activation of macrophage by cobalt-alloy particles resulted in a T helper 17 (Th17) cell inflammatory response, which is directly associated with the risk of osteolysis development (Chen et al, 2017). However, in a study using a mouse model, the intraarticular injection of CoCrMo particles induced a significantly enhanced pro-inflammatory cytokine expression (TNF-α, IL-6, and IL-1β) when compared to the intraarticular injection of CoCrMo ions (Cheng et al, 2020). On the other hand, the expression of CD3-positive cells in the synovial membrane of mouse knee did not increase in any of the groups (Cheng et al, 2020).…”
Section: Metal Wear Debrismentioning
confidence: 99%
“…In an earlier study, the current pin-on-plate setup including the lubricant has been found to produce particles which are comparable in size and morphology to clinically produced metal particles in joint revision. 30…”
Section: Particlesmentioning
confidence: 99%